Integrate-and-Fire Neuron Circuit Without External Bias Voltages - Park, Young-Soo; Woo, Sola; Lim, Doohyeok; Cho, Kyoungah; Kim, Sangsig (Frontiers in Neuroscience, 2021)
In this study, we propose an integrate-and-fire (I&F) neuron circuit using a p-n-p-n diode that utilizes a latch-up phenomenon and investigate the I&F operation without external bias voltages using mixed-mode technology computer-aided design simulations. The neuron circuit composed of one p-n-p-n diode, three MOSFETs, and a capacitor operates with no external bias lines, and its I&F operation has an energy consumption of 0.59 fJ with an energy efficiency of 96.3% per spike. The presented neuron circuit is superior in terms of structural simplicity, number of external bias lines, and energy efficiency in comparison with that constructed with only MOSFETs. Moreover, the neuron circuit exhibits the features of controlling the firing frequency through the amplitude and time width of the synaptic pulse despite of the reduced number of the components and no external bias lines.